Enhancing security in cryptographic algorithm based on LECCRS. (2017) - Mani, K.; Devi, A.
The efficiency of any cryptographic algorithms depends on both security and operational speed. When a message is encrypted using any cryptosystems it produces only one level of security because it converts the plaintext into ciphertext where the ciphertext is not easily tractable. To increase the security in any cryptographic algorithm, normally the size of the plaintext and key should be taken very largely. Further, additional levels of security have been introduced in this paper to enhance the security. For that, the message to be encrypted is encoded first so that original form of the message is altered called the first level of security. The encoded message is sometimes too large so that it is compressed which results in changing the encoded form of message called second level security. Finally, the compressed message is encrypted using any one of the public-key cryptosystems by determining the block size dynamically which produces the third level of security. Thus, an integrated approach is proposed called encoded compressed cryptosystem in this paper.